Project-Based Learning Through Digital Printing Techniques To Improve Students' Local Cultural Innovation Creativity - Sutianah, Cucu; Sobandi, Bandi (Universitas Pendidikan Ganesha, 2022)
Aligning the needs of students, vocational schools and the world of work, many of whom have failed due to low mastery of soft skills. The purpose of this study, to describe the Project-Based Learning (PjBL) model in the manufacture of batik products with the motif of the peacock ngibing batik on the local cultural heritage of Tasikmalaya, and Secondary Vocational Education (SMK). In this study, the author will design a motif inspired by the ngibing peacock motif combined with Tasikmalaya batik for adult women with digital printing techniques so that the younger generation is more familiar with and interested in Tasikmalaya batik. The making of this motif will then be made into sheets of primissima cotton cloth that can be used to meet the fashion needs of the target market. This study uses a mix method with a quasi-experimental approach, as well as data collection techniques using questionnaires, observations, in-depth interviews and documentation. The results of this research study illustrate that the inheritance of local culture in SMK uses the PJBL model in passing down creativity and innovation of crafts and batik/textile creations from generation to generation. The Tasikmalaya batik pattern has its own charm as well as a beautiful and beautiful character with a combination of bright colors and patterns derived from flora and fauna. The philosophical value contained in this batik is that the peacock symbolizes the beauty of nature with its various flora and fauna. Ngibing symbolizes the customs and culture of a harmonious and peaceful society. Through the combination of Tasikmalaya batik with street style, it is hoped that it will produce innovative works and convey the meaning of the philosophy contained in it. The added value of this design is that it maintains the work of Indonesian art which makes attractive fashion designs with contemporary styles that have more value in the eyes of the world.